The Relationship between Physical Activity and Menstrual Cycle 11th Grade Student of Kharisma Bangsa High School and its Review According to Islamic Views - Fakhri Faadillah Djashar; Sri Wahyu Herlinawati; Firman Arifandi (Junior Medical Journal, 2022)
Introduction: Mentruation is a sign that a woman has entered puberty. Menstrual cycle disorders are a problem that is quite often experienced by adolescents. Irregular menstrual cycles can be caused by various factors, one of which is physical activity. This study aims to find out whether there is a relationship between physical activity and menstrual cycle in 11th grade students of Kharisma Bangsa High School and its review according to islamic views. Method: This type of research is analytical with a cross-sectional approach and the way of determining the sample is total sampling. The sample in this study was a 11th grade student of Kharisma Bangsa High School with a total of 44 students. Data collection is carried out by questionnaires. Results: In this study, only 32 respondents fit the research inclusion criteria. From the results of statistical analysis, 5 (15.6%) respondents with light physical activity had a regular menstrual cycle. Meanwhile, 13 (40.6%) respondents with moderate physical activity and 3 (9.4%) respondents with heavy physical activity had irregular menstrual cycles. The results of the Chi-Square test obtained a p-value of 0.045 (0.05) which showed a significant relationship between physical activity and the menstrual cycle in 11th grade students of Kharisma Bangsa High School.Conclusion: There is a significant relationship between physical activity and the menstrual cycle. Physical activity can affect menstrual cycle irregularities. Therefore, it is recommended to pay attention to the type and duration of physical activity to be carried out.